The Concept of Moral Education in Tafsir Al-Maraghi: A Qualitative Study of the Interpretation of Surah Luqman Verses 12-19 - Fauzen Sugali; Hafid; Cecep Anwar (al-Afkar, Journal For Islamic Studies, 2026)
Moral education has an important role in building individual character based on Islamic values. Surah Luqman verses 12-19 are the main reference in the Qur'an which contains the teachings of moral education. This research aims to analyze the concept of moral education as explained in Tafsir Al-Maraghi and its relevance in the context of modern education. This research approach is qualitative with a content analysis method. Data were collected through literature studies on Tafsir Al-Maraghi and other supporting works related to moral education. The results of the study show that Tafsir Al-Maraghi emphasizes moral values that include human relationships with Allah (hablum minallah), fellow humans (hablum minannas), and the environment. Al-Maraghi's interpretation of these verses highlights the role of parents, especially fathers, in providing moral education through consistent example, advice, and teaching. In addition, Tafsir Al-Maraghi emphasizes the importance of moral formation through self-control, sincerity, and responsibility. This research discussion connects the relevance of moral teachings in Tafsir Al-Maraghi with contemporary educational practices, especially in building character-based educational curricula. This study concludes that the tafsir of Al-Maraghi makes a significant contribution in formulating an applicable moral education strategy for today's young generation. Thus, the moral values in Surah Luqman verses 12-19 can be used as a basis for building an ethical and moral society.